High-strength and high-plasticity Sn-based lead-free solder alloy suitable for SoC chip packaging

By designing a Sn-based lead-free solder alloy containing Ag, Cu, In, Bi, and Sb, the shortcomings of the existing Sn-Ag-Cu-based solder alloy in temperature cycling and temperature impact performance are solved, and high strength, high plasticity and good thermal fatigue reliability are achieved, which are especially suitable for SoC chip packaging.

CN119820173AActive Publication Date: 2025-04-15DALIAN UNIV OF TECH
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
CN202510181139.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-19
Publication Date
2025-04-15
Estimated Expiration
2045-02-19

AI Technical Summary

Technical Problem

The existing Sn-Ag-Cu-based lead-free solder alloys have shortcomings in temperature cycling and temperature impact performance, and cannot meet the needs of high-reliability packaging.

Method used

A high-strength, high-plastic Sn-based lead-free solder alloy was designed, containing 3.4% Ag, 0.4% Cu, 1.4~2.8% In, 1.3~2.6% Bi, 0.8~1.5% Sb, with a balance of Sn. By regulating the elemental ratio of In, Bi, and Sb, the alloy precipitates micron-level Bi-rich phase or InSb phase between β-Sn crystals, refines the β-Sn matrix, and improves the mechanical properties of the solder joints.

Benefits of technology

The Sn-based solder alloy has significantly improved its mechanical properties, and has the advantages of high welding strength, plasticity, good wetting, low cost, lead-free and environmentally friendly. It is especially suitable for SoC chip packaging, improving the thermal fatigue reliability such as temperature cycling and temperature impact of solder joints.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119820173A_ABST
    Figure CN119820173A_ABST
Patent Text Reader

Abstract

The invention discloses a high-strength and high-plasticity Sn-based lead-free solder alloy suitable for SoC chip packaging. The solder alloy comprises the following components in percentage by mass: 3.4% of Ag, 0.4% of Cu, 1.4%-2.8% of In, 1.3%-2.6% of Bi, 0.8%-1.5% of Sb and the balance of Sn. The atomic number ratio of the sum of Bi atoms and Sb atoms to In atoms is 1: 1; and a Sn-Ag-Cu-In-Bi-Sb six-element cluster formula: Sn < 260-4x > Ag < 10 > Cu < 2 > In < 2 x > Bi < x > Sb < x > is satisfied. The lead-free solder alloy disclosed by the invention has the processing property matched with that of a commonly used Sn-Ag-Cu alloy, good wettability and excellent mechanical property, and is particularly suitable for SoC chip packaging.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of solder alloys, and in particular relates to a Sn-based lead-free solder alloy with high strength and high plasticity. Background Art

[0002] As chips continue to develop towards large size, high computing power, high-density integration, high flow rate, and high reliability, SoC (System on a Chip) chips meet the performance and battery life requirements of mobile devices such as smartphones and tablets through their high integration and low power consumption. At the same time, SoC chips also face huge challenges in terms of reliability: on the one hand, the risks of warping and other risks faced by electronic devices during the packaging manufacturing process are more severe; on the other hand, the reliability requirements of the packaging during service are more stringent. The typical Sn-3.0Ag-0.5Cu solder currently used for packaging interconnection has problems such as poor temperature cycling and temperature shock performance, and can no longer meet the needs of high-reliability packaging. It is urgent to optimize the composition of the Sn-Ag-Cu lead-free solder alloy to improve the strength and plasticity of the solder joints, thereby improving the thermal fatigue reliability of the solder joints such as temperature cycling and temperature shock.

[0003] At present, several representative commercial doped solder alloys (usually adding elements such as Ni, Bi, Co, Ge, Ga, Sb, In, etc.), such as Ecolloy's SAC-R (Sn-0.92Cu-2.46Bi), Cyclomax's SAC-Q (Sn-3.4Ag-0.5Cu-3.3Bi), Alpha's Innolot (Sn-3.8Ag-0.7Cu-3Bi-1.45Sb-0.15Ni) and Senju's M794 (Sn-3.4Ag-0.7Cu-3.2Bi-3Sb-0.06Ni-0.01Co), have improved the strength on the basis of Sn-Ag-Cu alloy, but still have shortcomings such as insufficient temperature cycle life and poor plasticity, which cannot meet the current demand for high service reliability of solder alloys. Therefore, it is urgent to design and develop a Sn-based solder alloy with high strength and high plasticity to meet the current industrial application requirements. Summary of the invention

[0004] The purpose of the present invention is to overcome the defects of the prior art and provide a high-strength, high-plasticity Sn-based lead-free solder alloy which is suitable for SoC chip packaging, adapts to the current mainstream Sn-3.0Ag-0.5Cu solder alloy reflow process, has the advantages of high welding strength, high plasticity, low cost, lead-free, and environmental protection.

[0005] To achieve the above object, the technical solution adopted by the present invention is: The present invention provides a high-strength and high-plasticity Sn-based lead-free solder alloy suitable for SoC chip packaging. The solder alloy comprises the following components in mass percentage: 3.4% Ag, 0.4% Cu, 1.4-2.8% In, 1.3-2.6% Bi, 0.8-1.5% Sb, and the remainder is Sn; the atomic number ratio of the sum of Bi atoms and Sb atoms to In atoms is 1:1; and the Sn-Ag-Cu-In-Bi-Sb hexagram cluster formula is satisfied: Sn 260-4x Ag 10 Cu2In 2x Bi x Sb x .

[0006] Preferably, in the solder alloy, the mass content of In is 1.4%, the mass content of Bi is 1.3%, and the mass content of Sb is 0.8%; the Sn-Ag-Cu-In-Bi-Sb hexagram cluster formula is satisfied. 252 Ag 10 Cu2In4Bi2Sb2.

[0007] Preferably, in the solder alloy, the mass content of In is 2.1%, the mass content of Bi is 1.9%, and the mass content of Sb is 1.1%; the Sn-Ag-Cu-In-Bi-Sb hexagram cluster formula is satisfied. 248 Ag 10 Cu2In6Bi3Sb3.

[0008] Preferably, in the solder alloy, the mass content of In is 2.8%, the mass content of Bi is 2.6%, and the mass content of Sb is 1.5%; the Sn-Ag-Cu-In-Bi-Sb hexagram cluster formula is satisfied. 244 Ag 10 Cu2In8Bi4Sb4.

[0009] In view of the characteristics of Sn-Ag-Cu solder alloy, the present invention obtains the Sn-Ag-Cu ternary cluster formula [Sn-Ag 10 Cu2]Sn3+16{[Sn-Sn 10]Sn5. According to the principle of strong interaction: compared with Ag and Cu atoms, the mixing enthalpy of Bi, Sb, In and Sn atoms is the lowest, and Sn atoms are the matrix, so in the fourth, fifth and sixth component replacement processes, Sn atoms are replaced; in addition, since the number of outermost electrons of Sn atoms is 4, the number of outermost electrons of Bi and Sb atoms is 5, and the number of outermost electrons of In atoms is 3, in order to ensure that the number of atoms before and after the replacement remains unchanged, and the number of outermost electrons of the cluster remains consistent, the atomic ratio of the sum of Bi and Sb atoms to the number of In atoms is determined to be 1:1. Finally, combined with the saturated solid solubility limit of In, Sb and Bi elements in β-Sn, a Sn-Ag-Cu-In-Bi-Sb hexa-element alloy with a certain composition is obtained.

[0010] The present invention has the following beneficial effects: 1) By adjusting the element ratio of In, Bi and Sb, the alloy precipitates micron-sized Bi-rich phase or InSb phase between β-Sn crystals, refines the β-Sn matrix, improves the plasticity of the Sn-Ag-Cu solder alloy, and significantly improves the comprehensive properties of the alloy, especially the mechanical properties. The melting point is between 199 and 221 °C, and it has the advantages of good wettability, high welding strength, high plasticity, low cost, lead-free, and environmental protection. It is particularly suitable for SoC chip packaging.

[0011] 2) In the Sn-based solder alloy of the present invention, In can reduce the liquidus temperature of the solder, balance the effect of Sb on the melting point, so as to adapt to the existing process; generate the interface Cu6(Sn,In)5 intermetallic compound phase during brazing, improve the alloy wetting performance and interface bonding strength; at the same time, inhibit the generation of Cu3Sn intermetallic compound phase during aging, avoid the formation of Kirkendall voids; improve the joint strength, and can improve the joint ductility, thereby improving the mechanical properties of the solder joint before and after aging. Bi at room temperature (25 o C) has a solid solubility of 3% in β-Sn. At high temperature (125 oC) The solid solubility can be increased to 17%, so the Bi element added at room temperature can improve the strength and hardness of the solder through solid solution strengthening. In addition, the precipitated Bi can refine the solder structure. At high temperatures, especially during aging and temperature cycling, Bi can continuously dissolve in the β-Sn matrix, refine the matrix, and inhibit the coarsening of the Ag3Sn phase, thereby improving the mechanical properties of the solder alloy at high temperatures. Sb improves the hardness of the solder through solid solution strengthening, can significantly refine the solder structure, and continues to dissolve in the β-Sn matrix during the aging process, thereby improving the mechanical properties after aging. At the same time, In can increase the solid solubility of Bi in the matrix, so that the size of the precipitated Bi-rich phase is micron-sized. The smaller Bi particles can produce fine grain strengthening and dispersion strengthening effects on the solder matrix, thereby improving the strength and plasticity of the alloy at the same time. In can form InSb intermetallic compound phase with Sb at the β-Sn grain boundary. The size of InSb phase is micron-level. The smaller InSb phase can produce fine grain strengthening and dispersion strengthening effects on the solder matrix, thereby improving the strength and plasticity of the alloy at the same time. At the same time, the coexistence of In and Sb can avoid the continuous bidirectional phase transformation between β-Sn and γ (InSn4), thereby improving the alloy's resistance to thermal fatigue. BRIEF DESCRIPTION OF THE DRAWINGS

[0012] Figure 1 The microstructure diagram of the solder of the comparative example and the embodiment of the present invention; Figure 2 The Vickers hardness indentation diagram of the solder of the comparative example and the embodiment of the present invention; Figure 3 This is a diagram of the shear strength of BGA solder joints of the comparative example and the embodiment of the present invention; Figure 4 Graph showing shear displacement of BGA solder joints in comparative examples and embodiments of the present invention. DETAILED DESCRIPTION

[0013] The present invention is further described below in conjunction with specific embodiments, but the protection scope of the present invention is not limited in any way. Example 1

[0014] The high-strength and high-plasticity Sn-based solder alloy of this embodiment includes the following components in mass percentage: Ag 3.4%, Cu 0.4%, In 1.4%, Bi 1.3%, Sb 0.8%, and the balance is Sn.

[0015] The Sn-Ag-Cu ternary cluster model design process of this embodiment is as follows: Based on [Sn-Ag 10 Cu2]Sn3+16{[Sn-Sn 10 ]Sn5=Sn 260 Ag 10Cu2 model, 4 In atoms are used to replace 4 Sn atoms, and 2 Bi atoms and 2 Sb atoms are added to replace 2 Sn atoms respectively. Finally, Sn 252 Ag 10 Cu2In4Bi2Sb2, that is, Sn-3.4Ag-0.4Cu-1.4In-1.3Bi-0.8Sb (mass percentage).

[0016] The preparation method of the high-strength and high-plasticity Sn-based solder alloy of this embodiment comprises the following steps: 1) Weigh Sn, Ag, Cu, In, Bi, and Sb with a purity of 99.99% according to the mass ratio and place them in a quartz tube; 2) Use hydrogen flame to melt and seal one end of the quartz tube, melt the other end into a narrow opening, and use a vacuum pump to evacuate the tube to a vacuum degree of 1×10 -3 ~ 1×10 -4 Pa, exhaust the air in the tube, and then melt and seal the narrow opening; 3) Place the quartz tube in step 2) in a resistance furnace and heat it to 800-1000°C for smelting. After all components are melted, keep the temperature at 800-1000°C for 8-10 hours to homogenize the alloy. Rotate the quartz tube once every hour to ensure that the liquid alloy in the quartz tube is more uniform. 4) After the smelting is completed, take out the quartz tube and cool it to room temperature to obtain a high-strength and high-plasticity Sn-based solder alloy. Example 2

[0017] The high-strength and high-plasticity Sn-based solder alloy of this embodiment includes the following components in mass percentage: Ag 3.4%, Cu 0.4%, In 2.1%, Bi 1.9%, Sb 1.1%, and the balance is Sn.

[0018] The Sn-Ag-Cu ternary cluster model design process of this embodiment is as follows: Based on [Sn-Ag 10 Cu2]Sn3+16{[Sn-Sn 10 ]Sn5=Sn 260 Ag 10 Cu2 model, 6 In atoms are used to replace 6 Sn atoms, and 3 Bi atoms and 3 Sb atoms are added to replace 3 Sn atoms respectively. Finally, Sn 248 Ag 10 Cu2In6Bi3Sb3, that is, Sn-3.4Ag-0.4Cu-2.1In-1.9Bi-1.1Sb (mass percentage).

[0019] The preparation method of the solder alloy is the same as that of Example 1. Example 3

[0020] The high-strength and high-plasticity Sn-based solder alloy of this embodiment includes the following components in mass percentage: Ag 3.4%, Cu 0.4%, In 2.8%, Bi 2.6%, Sb 1.5%, and the balance is Sn.

[0021] The Sn-Ag-Cu ternary cluster model design process of this embodiment is as follows: Based on [Sn-Ag 10 Cu2]Sn3+16{[Sn-Sn 10 ]Sn5=Sn 260 Ag 10 Cu2 model, 8 In atoms are used to replace 8 Sn atoms, and 4 Bi atoms and 4 Sb atoms are added to replace 4 Sn atoms respectively. Finally, Sn 244 Ag 10 Cu2In8Bi4Sb4, that is, Sn-3.4Ag-0.4Cu-2.8In-2.6Bi-1.5Sb (mass percentage).

[0022] The preparation method of the solder alloy is the same as that of Example 1.

[0023] Comparative Example 1 The solder alloy of this comparative example includes the following components in mass percentage: Ag 3.4%, Cu 0.4%, In 3.6%, Bi 3.2%, Sb 1.9%, and the balance is Sn.

[0024] The Sn-Ag-Cu ternary cluster model design process of this comparative example is as follows: Based on [Sn-Ag 10 Cu2]Sn3+16{[Sn-Sn 10 ]Sn5=Sn 260 Ag 10 Cu2 model, 10 In atoms are used to replace 10 Sn atoms, and 5 Bi atoms and 5 Sb atoms are added to replace 5 Sn atoms respectively. Finally, Sn 240 Ag 10 Cu2In 10 Bi5Sb5, namely Sn-3.4Ag-0.4Cu-3.6In-3.2Bi-1.9Sb (mass percentage). Although this comparative example satisfies the cluster model, the composition range of In, Bi and Sb elements exceeds the composition range specified in the claims.

[0025] The preparation method of the solder alloy is the same as that of Example 1.

[0026] Comparative Example 2

[0027] The solder alloy of this comparative example includes the following components in mass percentage: Ag 3.4 %, Cu 0.4 %, In 4.2 %, Bi 4.5 % and Sb 1.9 %, with the balance being Sn.

[0028] The Sn-Ag-Cu ternary cluster model design process of this comparative example is as follows Based on [Sn-Ag 10 Cu2]Sn3+16{[Sn-Sn 10 ]Sn5=Sn 260 Ag 10 Cu2 model, 12 In atoms are used to replace 12 Sn atoms, 7 Bi atoms are added to replace 7 Sn atoms, and 5 Sb atoms are added to replace 5 Sn atoms. Finally, Sn 236 Ag 10 Cu2In 12 Bi7Sb5, namely Sn-3.4Ag-0.4Cu-4.2In-4.5Bi-1.9Sb (mass percentage). Although this comparative example satisfies the cluster model, the composition range of In, Bi and Sb elements exceeds the composition range specified in the claims.

[0029] The preparation method of the solder alloy is the same as that of Example 1.

[0030] Comparative Example 3

[0031] The solder alloy of this comparative example includes the following components in mass percentage: 3.0% Ag and 0.5% Cu, with the balance being Sn. This comparative example is a commercial composition that does not satisfy the cluster formula.

[0032] The preparation method of the solder alloy is the same as that of Example 1.

[0033] Comparative Example 4

[0034] The solder alloy of this comparative example includes the following components in mass percentage: 3.4% Ag, 0.5% Cu and 3.3% Bi, and the balance is Sn. This comparative example is a commercial composition that does not satisfy the cluster formula.

[0035] The preparation method of the solder alloy is the same as that of Example 1.

[0036] Comparative Example 5

[0037] The solder alloy of this comparative example includes the following components in mass percentage: 0.92% Cu and 2.46% Bi, and the balance is Sn. This comparative example is a commercial composition that does not satisfy the cluster formula.

[0038] The preparation method of this comparative example is the same as that of Example 1.

[0039] Comparative Example 6

[0040] The solder alloy of this comparative example includes the following components in mass percentage: Ag 3.8 %, Cu 0.7 %, Bi 3.0 %, Sb 1.45 % and Ni 0.15 %, and the balance is Sn. This comparative example is a commercial composition that does not satisfy the cluster formula.

[0041] The preparation method of the solder alloy is the same as that of Example 1.

[0042] Test Method

[0043] The solder alloys of the embodiments and comparative examples were subjected to DSC test, hardness test and shear performance test of BGA solder joints. The experimental conditions are as follows: 1) The heating rate of the DSC test is 10 °C / min. The test was performed using a differential scanning calorimeter, the sample mass was 30 mg, and the numerical processing was automatically calculated by the software. The intersection of the tangent of the endothermic peak and the extended line of the left baseline was defined as the solidus temperature, and the intersection of the tangent of the endothermic peak and the extended line of the right baseline was defined as the liquidus temperature of the alloy. The test results are shown in Table 1.

[0044] 2) Take a solder block of appropriate size and grind and polish it until the surface is bright and without obvious scratches. Place the solder block on the stage of the Vickers hardness tester, select a uniform position, select a 50 gf load, and the loading time is 10 s. The test results are shown in Table 1.

[0045] 3) Prepare comparative and example solder alloy solder balls with a diameter of 600 μm, apply a small amount of flux on the surface of the 600 μm solder ball, and accurately place it on a 500 μm pad of a printed circuit board (PCB), the pad material of which is a Cu substrate. After assembly, place it in a reflow oven and solder it according to the reflow method of a commercial SAC305 solder alloy, with a maximum temperature of 240 ~ 260 ℃ and a time exceeding the liquidus temperature of 60 ~ 120 s. Use a Dage 4000 solder strength tester to test the shear strength of the solder joint, with a pusher height of 45 μm and a shear speed of 500 μm / s. The test results are shown in Table 1.

[0046] Table 1 Test results of solder alloy properties of examples and comparative examples

[0047] As can be seen from Table 1, the solder alloys of Examples 1, 2, and 3 have better shear strength, shear displacement, and more suitable melting temperature than the solder alloys of Comparative Examples 1-6.

[0048] Figure 1The microstructure diagrams of Examples 1, 2, 3 and Comparative Examples 1-6. The microstructure of the example alloy is composed of β-Sn phase, Ag3Sn phase, Cu6Sn5 phase, and micrometer-sized Bi phase and InSb phase. The added In element is first dissolved in Ag3Sn; Bi and Sb elements are first dissolved in the β-Sn matrix; In can increase the solubility of Bi in the β-Sn matrix, and Bi exceeding the solubility will precipitate as a micrometer-sized Bi-rich phase. It can be seen from the microstructure in the figure that the microstructures of Examples 1, 2, and 3 are more uniform and fine than those of Comparative Examples 1-6.

[0049] Figure 2 The Vickers hardness indentation diagrams of Examples 1, 2, 3 and Comparative Examples 1-6. Comparative Examples 1-6 all showed obvious deformation and cracks, while the alloy body solders of Examples 1, 2, and 3 had no obvious cracks. This is because through the proportioning, the appropriate amount of In element and Sb element, In element and Bi element, In element and Bi, Sb element can be added in combination to generate micrometer-scale InSb phase and Bi phase at the grain boundary, strengthen the grain boundary, reduce brittleness while increasing hardness, and effectively hinder the expansion of cracks under stress. In addition, according to the results in Table 1, Examples 1, 2, and 3 have a lower Vickers hardness than Comparative Examples 1-6, and are not prone to stress transfer during thermal fatigue service, which has a great advantage in the practical application of solder alloys.

[0050] Figure 3 is the shear strength diagram of Examples 1, 2, 3 and Comparative Examples 1-6, Figure 4 It is the shear displacement diagram of Examples 1, 2, 3 and Comparative Examples 1-6. It can be seen from the figure that in the solder joints of Examples 1, 2 and 3 in which In element, Sb element and Bi element are added in a ratio within a specific range, In element and Bi, Sb element can make the solder joint have a higher shear strength, and at the same time greatly improve the shear displacement of the solder joint, and have good comprehensive mechanical properties. This is due to the synergistic effect of In element and Sb element, which generates micron-sized InSb phase at the grain boundary, reduces grain boundary energy, reduces the risk of brittle fracture, and improves solder joint ductility. In addition, the In element can increase the solid solubility of the Bi element in the β-Sn matrix, reduce the precipitation of large Bi phases in the matrix, and reduce the brittleness of the solder joint while improving the strength of the solder joint.

[0051] Through the performance comparison of the embodiments and the comparative examples, it can be seen that the Sn-based solder alloy of the present invention has higher welding strength, better plasticity, is lead-free and environmentally friendly, is more suitable for the current mainstream Sn-3.0Ag-0.5Cu solder alloy reflow process, and is particularly suitable for SoC chip packaging.

[0052] The above-mentioned embodiments only express several implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the patent application. It should be pointed out that, for a person of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A high-strength and high-plasticity Sn-based lead-free solder alloy suitable for SoC chip packaging, characterized in that: The solder alloy comprises the following components in mass percentage: 3.4% Ag, 0.4% Cu, 1.4-2.8% In, 1.3-2.6% Bi, 0.8-1.5% Sb, and the balance is Sn; the atomic number ratio of the sum of Bi atoms and Sb atoms to In atoms is 1:1; and the Sn-Ag-Cu-In-Bi-Sb hexagram cluster formula is satisfied: Sn 260-4x Ag 10 Cu2In 2x Bi x Sb x .

2. A high-strength and high-plasticity Sn-based lead-free solder alloy suitable for SoC chip packaging according to claim 1, characterized in that: In the solder alloy, the mass content of In is 1.4%, the mass content of Bi is 1.3%, and the mass content of Sb is 0.8%; the Sn-Ag-Cu-In-Bi-Sb hexagram cluster formula is satisfied. 252 Ag 10 Cu2In4Bi2Sb2.

3. A high-strength and high-plasticity Sn-based lead-free solder alloy suitable for SoC chip packaging according to claim 1, characterized in that: The solder alloy has an In content of 2.1%, a Bi content of 1.9%, and a Sb content of 1.1% by mass; and satisfies the Sn-Ag-Cu-In-Bi-Sb hexagram cluster formula Sn 248 Ag 10 Cu2In6Bi3Sb3.

4. A high-strength and high-plasticity Sn-based lead-free solder alloy suitable for SoC chip packaging according to claim 1, characterized in that: In the solder alloy, the mass content of In is 2.8%, the mass content of Bi is 2.6%, and the mass content of Sb is 1.5%; the Sn-Ag-Cu-In-Bi-Sb hexagram cluster formula is satisfied. 244 Ag 10 Cu2In8Bi4Sb4.

Citation Information

Patent Citations

  • Sn-Zn-Bi-base lead-free solder alloy for soft soldering of aluminum and copper

    CN103737195A

  • High-strength and high-conductivity compound lead-free high-temperature solder and preparation method thereof

    CN105033496A

  • Semiconductor device manufacturing method and junction assembly apparatus

    CN105679686A

  • Composite soldering paste and method for preparing BGA soldering balls / soldering spots with fine-grained beta-Sn crystal grains by applying composite soldering paste

    CN113798722A

  • In and Sb reinforced Sn24-x-yBi18InxSby low-temperature lead-free solder and preparation method thereof

    CN116493805A